Limitations in the energy balance when VGO/aqueous bio-oil mixtures are co-processed in FCC units - Panero, Melisa (2022)
The effect on the energy balance of a FCC unit after co-feeding the aqueous fraction of a bio-oil together with a vacuum gas oil (VGO) has been studied. The simulation program considers the interdependency relationship between the reaction and regeneration sections in the unit, where the heat of coke combustion has to sustain the energy requirements to preheat and vaporize the feedstock as well as the endothermic cracking reactions. The combustion of coke deposited on an equilibrium commercial FCC catalyst in cracking various bio-oil/VGO mixtures at 530 °C, with catalyst to oil relationships between 3 and 6 in a CREC Riser Simulator laboratory reactor, was investigated by means of thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC). Results showed that the heat from coke combustion is not enough to provide the energy needed in the unit when the amount of bio-oil in the feedstock is larger than 5 wt%, mainly due to the high content of water in the aqueous fraction of the bio-oil and to the lower heat of combustion of the coke formed in co-processing, as compared to the VGO alone.